PERAN GAYA KEPEMIMPINAN DAN ETOS KERJA DALAM MENINGKATKAN KOMITMEN AFEKTIF KARYAWAN PT. JANICO RAYA DI SEMARANG - Ayuda Musa'ada; Sri Wahyuni Ratnasari (Jurnal Ilmiah Penelitian Mahasiswa, 2023)
This research is realized with a description of the objectives and analysis of the influence of leadership style in increasing affective commitment and the level of work ethic. What is the role of work ethic on affective commitment and the role of work ethic in mediating the impact of leadership style on affective commitment. The population in this study are all employees of PT Janico Raya totaling 150 employees. The sample quantity used in this study was determined using the Slovin formula, which obtained a total sample of 109 people. The analytical method used is quantitative analysis using multiple linear regression analysis techniques. The results of the research hypothesis analysis show that leadership style influences work ethic. Leadership style has no significant effect on affective commitment. Work ethic has a positive effect on affective commitment and work ethic mediates the effect of leadership style on employee affective commitment. Keywords: Leadership Style, Work Ethic, Affective Commitment